Тиазоло(3,4-а)пиримидиниевые соли - Шульга, Сергей Иванович; Чуйгук, В. А. (My University, 1971)
4-аминотиазолы труднодоступны и по химическим свойствам отличны от 2-аминотиазолов. В работе показано, что соли 4-аминотиазолов реагируют с β-дикетонами с замыканием пиримидиниевого цикла и образованием производных с неизвестной ранее системой тиазоло (3,4-а)пиримидина. Полученные соединения не образуют полиметиновых красителей в отличие от тиазоло(3,2-а)пиримидиниевых солей.

4 aminothiazoles inaccessible and chemical properties different from the 2-aminothiazole. The paper shows that the salt of 4-aminothiazole react with β-diketones with the closure pyrimidine cycle and formation of derivatives with a previously unknown system thiazolo (3,4-a) pyrimidine. The resulting compounds do not form polymethine dyes unlike thiazolo (3,2-a) pirimidine salts.
Keywords: тіазол; aminothiazole; карбонильні з'єднання; хлорвинилкетон; carbonyl compounds; chlorovinylketone; кафедра харчової хімії